Ответ:
[tex]3-2\cdot (4-2x)-(6-3x)\cdot (-2)=8-3\cdot (2-2x)[/tex]
Раскрываем скобки и приводим подобные члены.
[tex]3-8+4x+12-6x=8-6+6x\\\\7-2x=2+6x\\\\7-2=6x+2x\\\\5=8x\\\\8x=5\\\\\bf x=\dfrac{5}{8}[/tex]
3-2×(4-2х)-(6-3х)×(-2)=8-3×(2-2х)
3-8+4х-(-12+6х)=8-6+6х
-5+4х+12-6х=2+6х
4х-6х-6х=5-12+2
-8х=-5
х=-5/(-8)
х=5/8
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]3-2\cdot (4-2x)-(6-3x)\cdot (-2)=8-3\cdot (2-2x)[/tex]
Раскрываем скобки и приводим подобные члены.
[tex]3-8+4x+12-6x=8-6+6x\\\\7-2x=2+6x\\\\7-2=6x+2x\\\\5=8x\\\\8x=5\\\\\bf x=\dfrac{5}{8}[/tex]
Ответ:
3-2×(4-2х)-(6-3х)×(-2)=8-3×(2-2х)
3-8+4х-(-12+6х)=8-6+6х
-5+4х+12-6х=2+6х
4х-6х-6х=5-12+2
-8х=-5
х=-5/(-8)
х=5/8